Soil carbon improvement under long‐term (36 years) no‐till sorghum production in a sub‐tropical environment. (22nd September 2020) - Govindasamy, Prabhu; Liu, Rui; Provin, Tony; Rajan, Nithya; Hons, Frank; Mowrer, Jake; Bagavathiannan, Muthukumar
Abstract: Soil organic matter (SOM) is considered an important indicator of soil quality, which can be impacted by crop production practices such as tillage. In this study, two long‐term tillage regimes (conventional tillage [CT] and no tillage [NT], conducted for 36 years) were compared in continuous sorghum production in a sub‐tropical environment in southeast Texas. The positive effects of long‐term NT practice were more conspicuous at the soil surface compared with the deeper soil profiles. The SOC was greater (1.5 t C ha −1 greater) in the NT system compared with the CT system. Results from an incubation study indicate that the rate of C‐min at 0–5 cm soil depth was significantly greater (164 μg of CO2 –C g −1 of soil greater) in NT than that of CT, but this trend was reversed at 10–20 cm depth wherein the C‐min rates were 106 μg of CO2 –C g −1 of soil greater in CT compared with NT, which is likely because of soil disturbance during the study. Soil cumulative CO2 ‐C emissions were greater in the CT system (7.28 g m −2 ) than in the NT system (5.19 g m −2 ), which is primarily attributed to high soil temperature conditions in the CT system. Sorghum grain yield however was not influenced by the differences in SOC content in this long‐term experiment. Overall, the present study found that long‐term conservation tillage improved SOC stock and reduced carbon loss, thus had a positive impact on soil health and sustainability.